Weak Instruments and Weak Identification in Estimating the Effects of Education on Democracy - Matteo Bobba; Decio Coviello (Inter-American Development Bank, Research Department, 2006)
Is there any relation between education and democracy? Once we correct for weak instruments and identify education as `weakly exogenous` we find new evidence that education systematically predicts democracy. Our results are robust across model specification, instrumentation strategies, and samples.
Keywords: 330; Bildungsniveau; Demokratie; Schätztheorie